The use of biogas in energetics - Sallai, László; Molnár, Tamás; Fodor, Dezső (Acta Agraria Debreceniensis, 2006)
In our study we examine the technical facilities of biogas production in the economic environment of a given region. The region can be considered as typical: it has animal farms, a poultry-processing plant with the characteristic problems of environment load and by-product handling. Biogas can be used for energetic purposes, and, in large scale, it can be sold as electric energy. The heat coming from the engine and the generator can be collected in heat exchangers and can be used for preparing hot water and for heating. One third of the gained energy is electric, two thirds are heat. The aim of the local owner and the economic management is to increase the rate of cost-effectiveness in general. We examined the tecnnical and economic conditions of establishing a biogas plant (using data of an existing pigfarm). We planned the biogas plant and calculated the expected investment and operational costs and return.